The development of Acceptance and Commitment Therapy Intervention (ACTI) module on mental health among students with a history of parental divorce - Charles Ganaprakasam; Murali Shanmugam; Kalaivani Ganasegaran (Penerbit Universiti Kebangsaan Malaysia, 2024)
Parental divorce presents a significant societal concern with profound implications for students' socio-emotional development. Despite increasing awareness of its negative impacts, tailored intervention programs addressing issues like suicidal ideation, depression, and resilience remain scarce. This study aims to evaluate the effectiveness of the Acceptance and Commitment Therapy Intervention (ACTI) Module in alleviating suicidal ideation and depression while enhancing resilience among primary school students from divorced households. Employing The Sidek module development model (SDMM), a comprehensive ACTI module was crafted, comprising six components with multiple units and activities. Preliminary findings suggests strong content validity and reliability of the ACTI module. Utilizing a quasi-experimental single group pretest posttest design with 30 participants aged 12, the study revealed significant improvements in depression symptoms, reductions in suicidal ideation, and enhancements in resilience levels post intervention. These results underscore the potential of the ACTI module in meeting the diverse needs of students from divorced families and supporting school counselors and psychologists in addressing mental health and resilience challenges effectively.